PENGARUH RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), DEVIDEN, DAN HARGA SAHAM TERHADAP RETURN SAHAM PERUSAHAAN SUB SEKTOR ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN PERIODE 2015-2017 - Synthia Dewi Anggira Sugiyani; Saryadi Saryadi (Universitas Diponegoro, 2019)
This study examined the effects of Return On Equity (ROE), Earning Per Share (EPS), dividends, and stock prices on stock returns. This type of research is explanatory with a quantitative approach. The sample in the study amounted to 9 insurance sub-sector companies listed on the Indonesia Stock Exchange which had gone public before the research period. Types of secondary data in the form of financial statements issued by the company. Data collection techniques in the form of documentary methods and literature studies. Data analysis used is multiple regression analysis and path analysis (path analysis) with the help of SPSS 21.0 for Windows. The classic assumption test is used to test whether the linear regression model has a classic assumption problem. This research is based on Markowitz's theory and signaling theory.The results showed that the regression model did not have the classic assumption problem. As well as the results of research on ROE, EPS, and dividends partially or simultaneously affect stock prices. And ROE, EPS, dividends, and stock prices simultaneously influence stock returns. And the results of the path analysis state ROE, EPS, and dividends through stock prices affect stock returns.